2019
DOI: 10.1111/all.13747
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transfer Protein allergy in the United Kingdom: Characterization and comparison with a matched Italian cohort

Abstract: Background Although pollen‐related food allergy occurs in all European populations, lipid transfer protein (LTP) allergy is considered to manifest mainly in Mediterranean countries. We aimed to characterize adults presenting with LTP allergy in a northern European country. Method The clinical history and sensitization patterns of subjects born and residing in the United Kingdom (UK), with a prior diagnosis of LTP allergy and sensitization to the peach LTP allergen Pru p 3, were compared to UK subjects with pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 43 publications
8
65
0
10
Order By: Relevance
“…A limitation of our study is the lack of data for Cor a 8 and other identified hazelnut allergen components. Cor a 8 is a common sensitizer in the Mediterranean area, although LTP sensitization is also increasingly demonstrated in non‐Mediterranean areas, but its clinical relevance is unclear . In the only eligible study from southern Europe included in this study, Cor a 8 sIgE levels in children were low and did not differ between allergic and tolerant subjects .…”
Section: Discussionmentioning
confidence: 82%
“…A limitation of our study is the lack of data for Cor a 8 and other identified hazelnut allergen components. Cor a 8 is a common sensitizer in the Mediterranean area, although LTP sensitization is also increasingly demonstrated in non‐Mediterranean areas, but its clinical relevance is unclear . In the only eligible study from southern Europe included in this study, Cor a 8 sIgE levels in children were low and did not differ between allergic and tolerant subjects .…”
Section: Discussionmentioning
confidence: 82%
“…LTP allergy is an increasingly common allergic syndrome . It affects Southern European countries to a greater extent, but its prevalence is also increasing in North and Central Europe . Peach LTP, Pru p 3, is the leading LTP sensitizer.…”
Section: Prescribing Immunotherapy To Pollens In Children: Influencmentioning
confidence: 99%
“…NSAIDs intake has been associated with food-induced anaphylaxis, [75][76][77][78][79] and these drugs can exacerbate food allergy in patients with food-dependent exercise-induced anaphylaxis. [80][81][82][83] [86][87][88] Concerning the association between food allergy and NSAIDs hypersensitivity, NSAIDs have been suggested to increase intestinal barrier permeability, enhancing allergen absorption.…”
Section: Food-dependent Nsaid-induced Anaphylaxismentioning
confidence: 99%